Contemporary anticoagulation therapy in patients undergoing percutaneous intervention. (April 2014) - Bhatty, Shaun; Ali, Asghar; Shetty, Ranjith; Sumption, Kevin F; Topaz, On; Jovin, Ion S
<x xml:space="preserve">Abstract</x> The proper use of anticoagulants is crucial for ensuring optimal patient outcomes post percutaneous interventions in the cardiac catheterization laboratory. Anticoagulant agents such as unfractionated heparin, a thrombin inhibitor; low-molecular weight heparins, predominantly Factor Xa inhibitors; fondaparinux, a Factor Xa inhibitor and bivalirudin, a direct thrombin inhibitor have been developed to target various steps in the coagulation cascade to prevent formation of thrombin. Optimal anticoagulation achieves the correct balance between thrombosis and bleeding and is related to optimal outcomes with minimal complications. This review will discuss the mechanisms and appropriate use of current and emerging anticoagulant therapies used during percutaneous interventions.